Market Channel Procurement Strategy and School Meal Costs in Farm-to-School Programs. (December 2019) - Fitzsimmons, Jill; O'Hara, Jeffrey K.
Abstract : Farm-to-school (F2S) local food procurement must be cost-effective to be financially sustainable without policy support. We test, among schools participating in F2S programs, whether market channel procurement strategies for local foods affect schools' perceptions of whether meal costs decline as a result of F2S participation. Schools that buy local foods exclusively from intermediaries are 7 percentage points less likely to report lower costs from undertaking F2S initiatives. We further demonstrate that the probability that schools source local foods exclusively from intermediaries is influenced by the number of direct marketing farmers in their county.